The World Bank Group’s Partnership with the Global Environment Facility : Volume 1. Main Report - Independent Evaluation Group (Washington, DC: World Bank, 2015)
The World Bank Group was a principal founding partner of the Global Environment Facility (GEF) in its pilot phase in 1991, and of the restructured GEF in 1994. The Bank plays three different roles in the GEF: (a) as trustee of the GEF and related trust funds, (b) as implementing agency, including the implementation of private-sector GEF projects by the International Finance Corporation (IFC), and (c) as the host organization of the functionally independent GEF secretariat.